A música sacra de Leo Schneider : uma voz no deserto - Dorfman, Paulo (2008)
This dissertation proposes an analysis of the sacred musical work by Porto Alegre composer Léo Schneider (1910-1978) based on a selection of his major sacred compositions. It emphasizes the uniqueness of Schneider s esthetic project and its possibilities as a tool for religious education. The first part of the research introduces Leo Schneider s personal history, from his family background to his formal and musical education, pointing out the environment in which he lived and the cultural, social and political background of his time. Musical aspects of the major Brazilian composers of his time and the international musical scenario of the period will also be taken into consideration. The focus is on sacred compositions of Schneider s time through a parallel between his work and that of his contemporaries, but the research also provides an understanding of his work within the context of protestant communities, especially Lutheran. The second part of the dissertation addresses the influence of Martin Luther s ideas on Leo Schneider s life and work, particularly the reformer s principles towards the meaning and the use of music in the church. The third part of the research analyzes five of Schneider s major sacred compositions, taking into account their musical and literary aspects so as to draw pedagogic connections in the fields of music, theology and religious education, stressing out the practical side of the composer, a diligent and creative artist at the service of the Gospel teaching through music.